Potensi Farmakologi dari Ekstrak Tumbuhan Berkhasiat sebagai Suplemen Antidiabetes, Antioksidan, dan Antimalaria - Marvina Marvina; Ardi Mustakim (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
Health is a condition where the body system and organs in the body can carry out their respective functions. However, in some cases that occur in Indonesian society, health problems have begun to appear, such as diabetes, malaria, and so on. According to the analysis, the incidence of diabetes continues to increase every year. Furthermore, the plant extract that is used as a source of antioxidants is bamboo shoots. The incidence of malaria resistance has reached >25% so that several drugs such as chloroquine are no longer used as the main drug in cases of malaria. The purpose of writing is to analyze the results of a review of the pharmacological potential of plant extracts that are effective as antidiabetic, antioxidant, and antimalarial supplements. The writing method used in writing this journal is to use a qualitative type. The results of the study are that bamboo leaf extract provides effectiveness as an antioxidant. Furthermore, antidiabetic can be found in the extract of the butterfly pea flower. Then the extract of the moon flower leaf has effectiveness as an antimalarial. The conclusion drawn is that the use of natural plant extracts can be used as antidiabetic, antioxidant, and antimalariall.